An Opinion Anomaly Detection Using K-Nearest Neighbours on Public Sector Financial Reports - Ahmad Dwi Arianto; Achmad Affandi; Supeno Mardi Susiki Nugroho (Institut Teknologi Sepuluh Nopember, 2018)
The Main Inspectorate (Itama) as internal auditor of BPK RI is obliged to protect the credibility and the honor of its institution. The opinion of financial statements is one of the BPK RI's products that become popular because of frequent bribery cases related to it. Typically, the bribe was given to change the opinion of the financial statements from an examined entity. The anomaly detection method becomes one of the alternative methods for filtering out reports with